Presence of tophi and carotid plaque were risk factors of MACE in subclinical artherosclerosis patients with gout: a longitudinal cohort study - Wang, Yu; Deng, Xuerong; Zhang, Xiaohui; Geng, Yan; Ji, Lanlan; Song, Zhibo; Zhang, Zhuoli (Frontiers in Immunology, 2023)
Background Patients with gout carry an excess risk for cardiovascular disease (CVD), but the contribution of subclinical atherosclerosis to the CVD risk has never been reported. In this study, we aimed to explore the predictive factors for incident major adverse cardiovascular events (MACE) in gout patients without a previous history of CVD or cerebral vascular disease. Methods A single-center, long-term follow-up cohort analysis was performed to assess subclinical atherosclerosis at baseline since 2008. Patients with a previous history of CVD or cerebrovascular disease were excluded. The outcome of the study was the first MACE. The presence of subclinical atherosclerosis was assessed by carotid plaque (CP), and carotid intima-media thickness (CMIT) was determined by ultrasound. An ultrasound scan of bilateral feet and ankles was performed at baseline. The association between tophi, carotid atherosclerosis, and the risk of developing incident MACE was evaluated using Cox proportional hazards models with adjustment for the CVD risk scores. Results A total of 240 consecutive patients with primary gout were recruited. Their mean age was 44.0 years, with male predominance (238, 99.2%). During a median follow-up of 10.3 years, incident MACE was ascertained in 28 (11.7%) patients. In a Cox hazards model, controlling for the CV risk scores, the presence of at least two tophi (HR, 2.12–5.25, p < 0.05) and carotid plaque (HR, 3.72–4.01, p < 0.05) were identified as independent predictors of incident MACE in gout patients. Conclusions The presence of at least two tophi and carotid plaque on an ultrasound could independently predict MACE in addition to conventional cardiovascular risk factors in gout patients.